The role of Adab al-Sultaniyyah in Fiqh al-Siyasah Alsyar`Iyyah: A comparative study between the works of al-Adab Alsultaniyyah and al-Ahkam al-Sultaniyyah / Ayidh Awwadh A Alharthi - Ayidh Awwadh , A Alharthi (2022)
Nothing of the Islamic thought remained except for two schools of jurisprudence (fiqh): Jurisprudence of Islamic Politics and the school of advice represented by the Islamic governance etiquettes. This study discussed the impact of the Islamic governance etiquette on jurisprudence of Islamic Politics. This study emanated from a basic supposition that reflects the governance etiquette being influenced by many various cultures that constitute it, particularly when the non-Islamic background influence on the governance etiquettes is transferred to the jurisprudence of Islamic politics. The importance of this study lies in the trial to separate the governance etiquettes from the jurisprudence of Islamic politics after the confusion overwhelmed many of the current researchers.The research aims at comparing the Islamic governance etiquettes to the jurisprudence of Islamic politics in terms of kinds of those who write about both of them, and their main topics and the renovation that attached to both, so that the researcher can identify the impact of the books of governance etiquettes on the jurisprudence of Islamic politics. The researcher adopted the analytical methodology and comparative methodology to achieve the study objectives.The dissertation concluded some results, the most important of which are what follows. The jurisprudence of Islamic politics is an independent knowledge and an integral part of the Islamic jurisprudence concerned on the state in Islam and the legislation of its regulations,in order that it realizes the public interest and does not contradict the rules and principles of the Islamic legislation. Second, the authors who write about the jurisprudence of Islamic politicsare from different careers and cultures. Writing about governance etiquettes continues because it does not require special capabilities or specifications. The influence of the governance etiquettes on the jurisprudence of Islamic politics was noticeable in the centrality of ruler and its call for political class, while it was not affected by the absence of a political theory representing it nor its call for unconditional obedience.